Community acquired pneumonia incidence before and after proton pump inhibitor prescription: population based study - Othman, Fatmah; Crooks, Colin J.; Card, Timothy R. (BMJ Publishing Group, 2016)
Objective To examine the risk of community acquired pneumonia before and after prescription of proton pump inhibitor (PPI) and assess whether unmeasured confounding explains this association. Design Cohort study and self controlled case series. Setting Clinical Practice Research Datalink (1990 to 2013) in UK. Participants Adult patients with a new prescription for a PPI individually matched with controls. Main outcome measures Association of community acquired pneumonia with PPI prescription estimated by three methods: a multivariable Cox model comparing risk in PPI exposed patients with controls, corrected for potential confounders; a self controlled case series; and a prior event rate ratio (PERR) analysis over the 12 month periods before and after the first PPI prescription. Results 160 000 new PPI users were examined. The adjusted Cox regression showed a risk of community acquired pneumonia 1.67 (95% confidence interval 1.55 to 1.79) times higher for patients exposed to PPI than for controls. In the self controlled case series, among 48 451 PPI exposed patients with a record of community acquired pneumonia, the incidence rate ratio was 1.19 (95% confidence interval 1.14 to 1.25) in the 30 days after PPI prescription but was higher in the 30 days before a PPI prescription (1.92, 1.84 to 2.00). The Cox regressions for prior event rate ratio similarly showed a greater increase in community acquired pneumonia in the year before than the year after PPI prescription, such that the analysis showed a reduced relative risk of pneumonia associated with PPI use (prior event rate ratio 0.91, 95% confidence interval 0.83 to 0.99). Conclusion The association between the use of PPIs and risk of community acquired pneumonia is likely to be due entirely to confounding factors.